INFLUENCE OF MODERNISM ON POST-INDEPENDENCE INDIAN ARCHITECTURE - Chhabra, Pankaj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The modern architecture, which was conceived as a reaction to the chaos and eclecticism of the earlier 19th century was taking its shape in the late 19th century and earlier 20th century. The exact timeline in which the modern movement in architecture started in the world cannot be described with precision. But ‘Modern architecture’ had its origin in the developments of the late 18th century with major thrust on the idea of progress. This movement of modern architecture in India started quite late in the first half of 20th century. Its development in India started with the isolated efforts of some foreign architects’ works. But the movement gained momentum only after the arrival of foreign trained Indian architects with imbibed policy of modernism in their mind. Final thrust to this movement was given by the political patronage bestowed upon the idea of modernism by the then Prime Minister Pt. Jawahar Lal Nehru, when he invited Swiss born French architect Le Corbusier to design the state capital city of Chandigarh. This paper delves upon the Influence of Modern architecture of these foreign architects built in India on the Post independence Indian architecture.